Effect of sevoflurane on grafted kidney function in renal transplantation - Park, Jin Ha; Lee, Jae Hoon; Joo, Dong Jin; Song, Ki Jun; Kim, Yu Seun; Koo, Bon-Nyeo (Korean journal of anesthesiology, 2012)
The objective of this retrospective study was to determine if there are any differences in grafted kidney function in recipients of kidney transplantation (KT) when donors and recipients were anesthetized with sevoflurane compared to desflurane. Seventy-three pairs of donors-recipients were anesthetized with sevoflurane (Sevo group) and 71 pairs were anesthetized with desflurane (Des group). We retrospectively investigated the blood urea nitrogen (BUN) levels, creatinine (Cr) levels, and estimated glomerular filtration rates (eGFR) of the recipients in both groups for 1 year postoperatively. We tested non-inferiority for serum creatinine at discharge and 1 year after KT. Short-term (1 year) outcomes of KT were assessed by the incidence of delayed graft function (DGF), acute rejection episodes (ARE), and graft failure. There were no differences in BUN, Cr, eGFR, or outcomes of KT at 1 year postoperatively. Specifically, the 95% confidence interval for the difference in creatinine levels between the Sevo and Des groups was less than the margin of equivalence at the time of discharge and 1 year after surgery. The occurrences of DGF, ARE, and graft failure were comparable between the groups. Compared to desflurane, sevoflurane had no adverse effects on grafted renal function or on the short-term outcome of renal transplantation.